'Ilm al-Ma'ãnĩ in Jawãhir al-Balãgah and al-Balãgah al-Wãḍiḥah (A Comparasion Study in The Aspects of Objectives, Content or Topics, Method, and Evaluation) - Edi Kurniawan Farid (JURNAL IJ-ATL, 2021)
مستخلص البحثمن أهم كتب البلاغة التي شاعت استفادتها لتدريس البلاغة في المدارس والمعاهد والجامعات في إندونيسيا هي كتاب جواهر البلاغة وكتاب البلاغة الواضحة. هدف هذا البحث إلى كشف ما يحتوي عليه هذان الكتابان والمقارنة بينهما  فيما يتعلق بعلم المعاني من ناحية الأهداف، والمحتوى أو الموضوعات، وطريقة العرض، والتقويم. استخدم هذا البحث المكتبي أسلوب التوثيق لجمع البيانات. أما مصادر البيانات فهي كتاب جواهر البلاغة وكتاب البلاغة الواضحة. ولتحليل البيانات اعتمد هذا البحث على ثلاثة أمور أساسية منها تخفيض البيانات، وعرض البيانات، والاستنباط. ونتائج البحث هي؛ الأولى من ناحية الأهداف ما وجد أي هدف سلوكي واضح في هذين الكتابين. والثانية من ناحية الموضوعات هناك فرق في موضوعات الدرس وترتيب مباحث علم المعاني. والثالثة من ناحية طريقة العرض، وقد نهج كتاب جواهر البلاغة على الطريقة القياسية، أما البلاغة الواضحة فنهج على الطريقة الاستقرائية. والرابعة من ناحية التقويم، لقد وفر هذان الكتابان الأمثلة العديدة الوافية في كل مبحث وموضوع. وبجانب آخر هذان الكتابان متساويان في أن كليهما ما زالا مستندين على المنهج السكاكي أي الموضوعات الواردة في كتب البلاغة السكاكية، لأنهما يشتملان على الموضوعات والتقسيمات قدمها السكاكي وتلاميذه.الكلمات المفتاحية: جواهر البلاغة، البلاغة الواضحة، علم المعاني، بلاغةAbstractSome of the most important book of balãgah which is widely used for teaching balãgah in schools, islamic boarding schools, and universities in Indonesia is the book of jawãhir al-balãgah and al-balãgah al-wãḍiḥah. This research aims to discover what is contained in these two books and compare them with concerning at 'ilm al-ma'ãnĩ in the aspects of objectives, content or topics, method, and evaluation. This library research use the documentation technique for collecting data. The data resources are the book of jawãhir al-balãgah and al-balãgah al-wãḍiḥah. For analyzing the data, this research use three basic steps; data reduction, data presentation, and conclusion. The results of this research are; first, in the aspects of objectives, there wasn't any behavioural objective found in these two books. The second, in the aspects of content or topics, there is a difference in a few of the lesson topics and the order of 'ilm al-ma'ãnĩ's topics. Third, in the aspects of method, the book of jawãhir al-balãgah was approached in deductive methode, and al-balãgah al-wãḍiḥah was approached in inductive methode. Fourth, in the aspects of evaluation, these two books were completed by many adequated examples in each lesson and topic. On the other hand, these two books have the same condition that both of them are still based on the Sakkãkĩ's method, that is, the topics were contained by balãgah Sakkãkĩyah, because those two books contained the topics and categories presented by Sakkãkĩ and his students.Keywords: Jawãhir al-Balãgah, al-Balãgah al-Wãḍiḥah, 'Ilm al-Ma'ãnĩ, Balãgah